2006
DOI: 10.1155/ijrm/2006/71302
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Study of Friction Damping Blade Attachments of Rotating Bladed Disks

Abstract: In order to mitigate high cycle fatigue risks in bladed disks, the prediction of the vibration levels early in the design process is important. Therefore, the different sources of damping need to be modeled accurately. In this paper the impact of friction in blade attachments on forced response is investigated both numerically and experimentally. An efficient multiharmonic balance method is proposed in order to compute the forced response of bladed disks with contact and friction nonlinearities in blade roots.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 23 publications
0
70
0
Order By: Relevance
“…Many reduced-order modelling techniques dedicated to the mistuning of bladed disk can be found in the literature [33][34][35][36][37][38][39][40], and prove very efficient as long as the study is focused on linear structures. However, taking into account nonlinearities in the simulations can be of primary importance in the design process since they are known to have a strong impact on the vibration level, as pointed out in several numerical and experimental investigations [41][42][43]. A detailed review on vibration prediction of bladed disks in the presence of friction phenomena can be found in [44].…”
Section: Numerical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many reduced-order modelling techniques dedicated to the mistuning of bladed disk can be found in the literature [33][34][35][36][37][38][39][40], and prove very efficient as long as the study is focused on linear structures. However, taking into account nonlinearities in the simulations can be of primary importance in the design process since they are known to have a strong impact on the vibration level, as pointed out in several numerical and experimental investigations [41][42][43]. A detailed review on vibration prediction of bladed disks in the presence of friction phenomena can be found in [44].…”
Section: Numerical Applicationsmentioning
confidence: 99%
“…Here, one nonlinear mode is computed -using the azimuthal DOFs of the observation node as a control coordinate -and is associated to the first bending motion of the blade. The nonlinear forces are computed by means of the dynamic lagrangian frequency-time (DLFT) procedure described in [22,43], using a friction coefficient of 0.15 and an initial normal load of 200N corresponding to the contact pressures extracted from the nonlinear static analysis. The eigenvectors ϕ k and the eigenvalue λ are computed for a control coordinate sweeping through the range [0 -0.45]mm with a step of 0.005mm.…”
Section: Finite Element Modelmentioning
confidence: 99%
“…Nacivet et al [5] have proposed an original strategy -named the Dynamic Lagrangian FrequencyTime method (DLFT ) -based on augmented Lagrangian to deal with non-smooth contact-friction laws. This method was later used for the study of friction mechanisms in blade attachments [20]. In the present study, a similar approach is used but the formulation is presented using a mixture of relative displacement in the normal direction and relative velocity for the tangential directions of the contact interface.…”
Section: Contact Forces Calculationmentioning
confidence: 99%
“…To each penalty term, is associated a penalty coefficient, ε t and ε n respectively. A good choice for these parameters consists in ensuring that penalty terms balance with stiffness terms (Charleux et al [20] suggested to use a value close to the spectral radius of Λ(ω)).…”
Section: Penalty Function In the Frequency-domainmentioning
confidence: 99%
“…The commonest sources ( Fig. 1) of friction damping in turbine bladed disks are the bladedisk interfaces (Petrov & Ewins, 2005;Charleux et al, 2006;Allara et al, 2007), the shrouds (Yang & Menq, 1998c;Petrov & Ewins, 2003;Siewert et al, 2009) located at the blade tip in order to connect adjacent blades by interference, and underplatform dampers (Csaba, 1998;Yang & Menq, 1998a-b;Sanliturk et al, 2001;Panning et al, 2003;Petrov & Ewins, 2007;Zucca et al, 2008;Cigeroglu et al, 2009;Firrone et al, 2011), metal devices located under the blade platforms and pressed against them during rotation by the centrifugal force. In order to compute the forced response of bladed disks with friction contacts, commercial finite element codes are not suitable since they are based on the time integration method of the non-linear differential balance equations and they require very large calculations times, which make unfeasible any parametric analysis typical of the design phase.…”
Section: Introductionmentioning
confidence: 99%